2016 Computing in Cardiology Conference (CinC) 2016
DOI: 10.22489/cinc.2016.076-143
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Transient Outward Potassium Current on Action Potential Upstroke Velocities Tested Using the Dynamic Clamp Technique

Abstract: The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Thirdly, we assessed upstroke velocities in the HEK293-Na V 1.5 cells, transfected with either IRES-GFP or KCND3 -IRES-GFP plasmids. Noteworthy, HEK293 cells expressing Na V 1.5 display fast depolarizations upon switching from voltage clamp (VC) to current clamp (CC) due to Na + channel activation as previously shown (Berecki et al, 2010 ; Verkerk et al, 2016 ; Lieve et al, 2017 ). Thus, the alternating VC/CC technique allows for a more dynamic assessment of Na V 1.5 current as compared to measurements in VC configuration, in the setting of more physiological temperature and Na + gradients across the membrane.…”
Section: Resultsmentioning
confidence: 67%
See 2 more Smart Citations
“…Thirdly, we assessed upstroke velocities in the HEK293-Na V 1.5 cells, transfected with either IRES-GFP or KCND3 -IRES-GFP plasmids. Noteworthy, HEK293 cells expressing Na V 1.5 display fast depolarizations upon switching from voltage clamp (VC) to current clamp (CC) due to Na + channel activation as previously shown (Berecki et al, 2010 ; Verkerk et al, 2016 ; Lieve et al, 2017 ). Thus, the alternating VC/CC technique allows for a more dynamic assessment of Na V 1.5 current as compared to measurements in VC configuration, in the setting of more physiological temperature and Na + gradients across the membrane.…”
Section: Resultsmentioning
confidence: 67%
“…Using dynamic clamp, we have recently assessed the effect of an I to -like current on the upstroke velocity in HEK293 cells transiently overexpressing Na V 1.5 channels. That study revealed only a minor influence of I to , if any, on upstroke velocity (Verkerk et al, 2016 ). Here, we confirmed these results using computer simulations based on the current densities recorded (Figure 5 ).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…However, a recent study in HEK293 cells, combining in silico injection of I to using dynamic clamp with measurement of I Na -driven upstrokes using alternating voltage clamp/current clamp demonstrated that I to hardly affected upstroke velocity. 28 Furthermore V max can be influenced by sodium channel availability, which is set by both the resting ) cycling, which may modulate I Na . 29 It can be speculated that a decrease in Ca 2+ i may result in a faster V max .…”
Section: Hey2mentioning
confidence: 99%